1991
DOI: 10.1111/j.1745-4565.1991.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Irradiation Technology for Improved Shellfish Sanitation

Abstract: Ionizing radiation is shown capable of serving as an effective sanitizing treatment improving the sanitary quality of shellfish and providing an increased margin of safety for shellfish consumers. 60Co irradiation of the hard‐shelled clam, Mercenaria mercenaria, and the oyster, Crassostrea virginica, significantly reduced virus carriage numbers without unduly affecting shellfish survival rates or desirable organoleptic qualities. A D10 value of 2 kGy was determined for depletion of hepatitis A virus in clams a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…There is a linear relationship between dose and level of virus inactivation. This linear relationship between virus inactivation and ionizing radiation has been reported earlier (2,26,35). Poliovirus exhibited greater resistance to E-beam irradiation than did rotavirus (Table 1).…”
Section: Discussionsupporting
confidence: 50%
“…There is a linear relationship between dose and level of virus inactivation. This linear relationship between virus inactivation and ionizing radiation has been reported earlier (2,26,35). Poliovirus exhibited greater resistance to E-beam irradiation than did rotavirus (Table 1).…”
Section: Discussionsupporting
confidence: 50%
“…A D 10 value of 13.5 kGy was reported for F coliphages (12). Mallet et al (27), when employing gamma irradiation, reported no significant difference in the inactivation of viral pathogens, reporting D 10 values of 2.02, 3.1, and 2.4 kGy for HAV, poliovirus I, and rotavirus SA11, respectively. As stated earlier, we are not aware of any published studies on enteric viruses in whole oysters treated with E-beam irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma radiation as a sanitization treatment for shellfish has been studied by different research groups (12,16,(25)(26)(27)(28). A variety of bacterial pathogens are susceptible to ionizing radiation, such as Vibrio cholerae, V. parahaemolyticus, and V. vulnificus, with D 10 values as low as 0.1 kGy (27,29). Inactivation studies on Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, MNV-1 is much more resistant than FCV and CaCV to gamma irradiation. Irradiation of other food-borne and waterborne viruses, such as hepatitis A virus (HAV) (9), rotavirus (41), and poliovirus (27), has been reported. It was found that the D 10 values (dose required to reduce infectivity by 1 log 10 ) for HAV in lettuce and strawberries were 2.72 Ϯ 0.05 and 2.97 Ϯ 0.18 kGy, respectively (9), while the D 10 value for gamma irradiating HAV in clams and oysters was 2 kGy (41).…”
Section: Discussionmentioning
confidence: 99%